Conditional critical thinking gains: ATI study of homo complexus in PBL–SSI biology education - Ida Ayu Purnama Bestari; Anantawikrama Tungga Atmadja; I Nyoman Tika; I Wayan Suastra (University of Muhammadiyah Malang, 2025)
This quasi-experimental study investigated the effectiveness of a Homo Complexus (HC)-framed Problem-Based Learning and Socio-Scientific Issues (PBL–SSI–HC) model in fostering critical thinking (CT) among biology education students (N=78). Comparing PBL–SSI–HC (n=38) with conventional PBL–SSI (n=40), a validated and reliable CT instrument was used for pretest and posttest. ANCOVA results revealed a significant Group × Pre_CT interaction (F (1, 74) = 7.73, p = .007, ηp² = 0.095), indicating that the model's effect on CT was conditional on initial CT levels. Simple slopes analysis showed that the PBL–SSI–HC model significantly benefited students with higher initial CT (adjusted mean difference = 0.079, p = .006, Hedges’ g = 0.19 at +1 SD Pre_CT), while advantages for lower and average baseline students were negligible. This aptitude–treatment interaction (ATI) suggests that the epistemic complexity of the Homo Complexus framework is most effective for learners with stronger prerequisite CT strategies. Instructional implications highlight the need for targeted scaffolding, such as explicit modeling of CT moves and structured argumentation, to extend these benefits across all CT ability levels and align with national educational goals.